Prostituição feminina na tríplice fronteira: uma etnografia no Motel Belize - Lorenzi, Glaucia (2019)
This dissertation presents an ethnography of female prostitution that occurs in a particular motel in the city of Foz do Iguaçu, presenting the relations of interaction and sociability. Therefore, it was necessary to analyze how the prostitutes use representation to win clients and face stigma, check how they react to the insertion of new individuals and understand how the interaction of group members occurs in different situations. The data collection of the present study is based on the ethnographic understanding of Gluckman (1980); Laplantine (2012); Malinowski (1978/1980) and Winkin (1998). Data analysis follows the logic of representations (GOFFMAN, 2009). To address prostitution and stigma were used the contributions of Alves (2014); Gaspar (1985); Goffman (1982); Julian (2002/2019); Martin (2003); Prada (2018); etc. Among other results, the observations allowed me to perceive the occurrence of innumerable simulations by the actors involved in order to reach objectives and allowed me to reflect on the masks we wear daily. It was clear that in the case of prostitution performed by this group, the representations contribute to transmit the image expected by society and to avoid stigma.